CRIMINAL LIABILITY FOR PERFORMERS OF THE PERSECUTION OF RELIGIOUS FIGURES IN INDONESIA - Fitri Wahyuni; Aris Irawan; Siti Rahmah (JCH (Jurnal Cendekia Hukum), 2021)
Persecution is a crime that is against the law in which the perpetrator must be sanctioned in accordance with the actions he committed. Refers to recent phenomenon, Persecution is happening againt religious leaders in Indonesia today. This is in the public spotlight because the perpetrators of persecution of religious figures according to the assumption of the perpetrators are mentally ill. In this study, the researcher used normative legal research methods. The type of data used in this research is secondary data and tertiary data. After the data is collected, then the data is analyzed and compiled using descriptive analysis and deductively deduced from general things to specific things. The results of the study state that perpetrators of persecution of religious figures can be held by legal liability for the crime and must comply with the elements contained in the Criminal Code. Criminal liability for perpetrators of persecution of religious figures depends on the results of examinations that have been carried out by a psychiatrist, then the judge will judge whether the psychological condition experienced by the perpetrator has influenced his actions or not.